Student Tolerance through Religious Moderation Values in Aswaja Courses - Ashoumi, Hilyah; Hidayatulloh, M Kris Yuan; Hasanah, Siti Da’watul; Umami, Fahmi Najah (Al-Tadzkiyyah: Jurnal Pendidikan Islam, 2023)
The purpose of this study is to describe the process of internalisation of religious moderation values in Aswaja course and its implication on students' tolerance attitude. This research is included in research that uses a phenomenological approach using qualitative research. This approach requires a number of assumptions that are different from the way used to approach people's behaviour with the intention of finding "facts" or "causes". Data collection techniques using observation, interviews, and documentation. The results of this study resulted in four strategies for internalising the values of religious moderation in the learning process of Aswaja courses at KH. A. Wahab Hasbullah University, among others; Learning planning in which there are topics regarding the prevention of radicalism, the use of constructive-based presentation methods in the learning process and evaluation of field assignments. The impact on the dominance of mutual respect between students with each other, students understand the existence of differences in scientific opinions that are furu'iyyah and ushuliyah and understand how to react to them.